Exploration of handwritten allographic features attributed to the primary educational backgrounds of Malaysian writers for forensic comparison - Gannetion, Linthini A/P (2023)
Class characteristics in handwritings is useful in writer profiling when exemplar samples are unavailable for comparison. The unique education system in Malaysia may have established specific characteristic handwritten allographic features that deserve investigation within the intelligence context. This study aims to investigate the common and distinguishable handwriting allographic features attributed to the primary education backgrounds of Malaysian writers for forensic comparison. At the preliminary stage, 50 sets of handwriting samples regardless of primary education background were thoroughly reviewed to determine the general handwritten features. Subsequently, characteristic handwritten features potentially attributed to the primary education backgrounds (i.e., National Schools, Chinesemedium vernacular schools, Tamil-medium vernacular schools, and Islamic Religious Schools) were identified and their associations among the four backgrounds were analysed using Chi-square test followed by multinomial logistic regression (MLR). Selected handwritten features were then examined on newly recruited 400 writers (100 writers for each background) in the field study. A classification and regression tree (CART) was established, and the predictive capability was determined using blind exemplars. From a total of 189 features determined at the preliminary stage, 23 of them were significantly attributable to primary education backgrounds (p-value <0.05) based on the Chi-square test and MLR model. In the field study, the number of statistically significant features were further reduced to 17 features, comprising of letters ‘B’, ‘D’, ‘E’, ‘G’, ‘H’, ‘I’, ‘p’, and ‘t’, and nine features were recognised to be capable of distinguishing writers from a single education background from the others. Through CART, five handwritten features carrying greater importance in discriminating the writers were determined, including letter ‘t’ with crossbar written first followed by vertical stroke, letter ‘B’ with no protruding initial stroke, letter ‘E’ constructed with three individual strokes, letter ‘E’ with the stem written first followed by the top arm, crossbar and base arm, and letter ‘G’ with stress written first followed by chin and barb. It allowed for a 71.0% accurate classification, and testing on blind exemplars demonstrating an 85.0% prediction accuracy. To conclude, this study had successfully determined the handwritten allographic features attributed to the primary educational backgrounds of Malaysian writers, providing the foundation data for the establishment of forensic intelligence framework for handwriting examination, which would be beneficial to the investigation of document related cases, especially when reference samples are not available.